Studi Sistem Dispersi Padat Klaritromisin – Eudragit L100 - Yuska Noviyanty; Elfi Sahlan Ben; Erizal Zaini (Jurnal Sains Farmasi & Klinis, 2016)
Solid dispersion made with the weight ratio (b/b) using the dissolving method. DTA analysis of the solid dispersion obtained in Eudragit L 100 affects the position and sharpness of the peak. X-ray diffraction analysis showed that of clarithromycin - Eudragit L 100 is in amorphous form and did not produce a new crystalline phase. SEM analysis showed that crystalline of Eudragit L 100 is smaller (amorphous) and stick to the surface of the clarithromycin crystal. IR spectrophotometer analysis showed that there is no chemical interaction between clarithromycin and Eudragit L 100. Clarithromycin assay was done by HPLC method, using mobile phase methanol and 0.067 M KH2PO4 (13:7) plus fospat acid pH 4.0. The dissolution profile by the time of 60 minutes are clarithromycin 45.73%, CF (1:1) 49.86%, DP (1:1) 51.53%, DP (2:1) 55.87% and DP (1:2) 58.97% respectively. Solid dispersion 1:2 (w/w) have an increased dissolution rate compared to clarithromycin.